Psychopathological factors associated with problematic alcohol and problematic Internet use in a sample of adolescents in Germany - Wartberg, Lutz; Brunner, Romuald; Parzer, Peter; Fischer-Waldschmidt, Gloria; Resch, Franz; Kaess, Michael (Psychiatry research, 2016)
In Germany, high prevalence rates for problematic alcohol use and problematic Internet use in adolescents were reported. The objective of the present study was to identify psychopathological factors associated with these two behavior patterns. To our knowledge, this is the first investigation assessing psychopathological factors for both problematic alcohol and problematic Internet use in the same sample of adolescents. We surveyed a sample of 1444 adolescents in Germany regarding problematic alcohol use, problematic Internet use, psychopathology and psychological well-being. We conducted binary logistic regression analyses. 5.6% of the sample showed problematic alcohol use, 4.8% problematic Internet use, and 0.8% both problematic alcohol and problematic Internet use. Problematic alcohol use was higher in adolescents with problematic Internet use compared to those without problematic Internet use. Conduct problems and depressive symptoms were statistically significant associated with both problematic alcohol and problematic Internet use. Prosocial behavior was related to problematic Internet use. Male gender and less peer problems were associated with problematic alcohol use. For the first time associations between adolescent problematic alcohol and problematic Internet use due to common psychopathological factors were identified. However, in addition to shared factors, we found also specific psychopathological correlates associated with these two behavior patterns.